Peningkatan Hasil Belajar Matematika Menggunakan Metode Tutor Sebaya Siswa Kelas VII Pada Materi Bentuk Aljabar (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
This study aims to improve students' mathematics learning outcomes of class VII G SMPN 48 Surabaya by applying the Tutor Sebaya method of learning. This research is a classroom action research (PTK). The subjects of the study were Class VII G SMPN 48 Surabaya, amounting to 38 students. The indicator of success in this study is determined by 70% of students complete learning. This research was conducted in two cycles with four stages of implementation, namely action planning, action implementation, observation or evaluation, and reflection. Data collection techniques of this study are tests, observations and documents. The results of this study indicate that the application of peer tutoring method on the subject of Algebra Shape can improve student learning outcomes of class VII G SMPN 48 Surabaya. This is shown in the improvement of the learning outcomes of each cycle that is on the pre-cycle result percentage of completeness of 23.68% has not reached the criteria of success, as well as in the first cycle of the completion percentage of 36.84% has not reached the criteria of success, as well as on the second cycle of the completion percentage of 71.05% has reached the expected success criteria. Keywords : Peer tutor method, the result of learning mathematics